(untitled) (Registros. Revista de Investigación Histórica, 2025)
This issue offers a historical perspective on urban riverbanks, understood as contact zones between city and water that exhibit complex physical, social, and cultural characteristics. Unlike other urban areas, riverbanks are both constrained and changing spaces, shaped by tensions between productive, recreational, infrastructural, and environmental uses. The articles in this dossier present research on various issues affecting these areas, such as major infrastructure projects; the spatialities, practices, and social interactions related to water and the beach; the role of riverbanks in socio-environmental conflicts in metropolitan areas; and the forms of social appropriation of coastal edges. Through case studies from Argentina, Brazil, Chile, and Spain that address different scales and temporalities, the dossier demonstrates how riverbanks have been—and continue to be—key sites for understanding urban history and the struggles over space in cities.